Perceived Quality Improvements Using Daily Allocation of Surgical Residents to the Operating Room and Outpatient Clinics. (24th October 2013) - Wirth, Keith; Leung, Patricia; Patcha, Prasanth; Sanni, Aliu
Abstract : Introduction. Balancing efficiency and quality in resident education and clinical care is challenging, particularly in a large tertiary center with resident work hour restrictions. This study investigates the use of daily allocation of surgical residents to operative cases and clinics with the goal of improving patient care, resident education, and coverage. Methods. Surgical residents were allocated to cases and clinic activities a day ahead, with a central email generated and sent to all surgical staff the day prior to the procedures and duties. A ten-item questionnaire was administered to the staff on the surgery service before and after this intervention, evaluating perceptions of educational experience, patient care, and coverage of operative cases, clinic, and floor duty. Results. A total of 28 staff members participated. No significant difference was found in the perception of stress at work, coverage of OR cases, or clinic attendance after the intervention. However, a statistically significant increase (p < 0.05 ) was noted in the perception of resident's educational experience in the clinic (39% vs. 94%), appropriate case distribution (54% vs. 94%), and quality of patient care (50% vs. 100%). Conclusions. Daily allocation of surgical residents to operative cases and clinic activities improves perceptions of resident educational experience and quality of patient care in a busy clinical setting.